Harnessing Rural Radio for Climate Change Mitigation and Adaptation in the Philippines - Navarro, Rex L.; Celeridad, Renz Louie V.; Matalang, Rogelio P.; Tabbun, Hector U.; Sebastian, Leocadio S. (2019)
The working paper documents the pilot rural radio campaign, dubbed as 'Climate Change i-Broadkas Mo', implemented by the CGIAR Research Program on Climate Change, Agriculture and Food Security in Southeast Asia (CCAFS SEA) and the Philippine Federation of Rural Broadcasters (PFRB)​ in strategic regions of the Philippines from 2015 to 2018. The radio campaign provided PFRB affiliated broadcasters with scripts and ready-to-be-aired (RTBA) interviews on climate-smart agriculture. The lessons learned from the project can be used to enhance the capacities of rural broadcasters on climate change reporting and to create a demand for radio-based distance learning, not only in Northern Philippines, but in similar regions in Southeast Asia.